2011
DOI: 10.1007/s11595-011-0294-1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of alumina addition on the optical property of zirconia/alumina composite dental ceramics

Abstract: The influence of various alumina additions on the optical property of zirconia/alumina composite ceramics was investigated. The relative sintered densities, transmittances, color and the microstructure of the composite ceramics were studied. The experimental results showed that the relative sintered densities and transmittances decreased with alumina addition. The lightness increased obviously but the chroma change was small. Pure zirconia nanopowders sintered densely could obtain the relatively high transmitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
(16 reference statements)
1
0
0
Order By: Relevance
“…influences the microstructure and retards the hydrothermal degradation of Y-TZP without compromising its mechanical properties [25]. However, Al2O3 can drastically decrease the translucency of zirconia ceramics [25][26][27], in agreement with the lowest TP observed in this study for GC ST that revealed the highest Al2O3 amount (0.36 wt%). As expected, a small amount of HfO2 (<5 wt%) was identified in all investigated zirconia grades.…”
Section: Discussionsupporting
confidence: 88%
“…influences the microstructure and retards the hydrothermal degradation of Y-TZP without compromising its mechanical properties [25]. However, Al2O3 can drastically decrease the translucency of zirconia ceramics [25][26][27], in agreement with the lowest TP observed in this study for GC ST that revealed the highest Al2O3 amount (0.36 wt%). As expected, a small amount of HfO2 (<5 wt%) was identified in all investigated zirconia grades.…”
Section: Discussionsupporting
confidence: 88%